2004
DOI: 10.1299/jsmea.47.98
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of Slip Bands near Twin Boundary in High-Cycle Fatigue

Abstract: In order to investigate the criterion for the persistent slip band (PSB) formation near a Σ3(111) coherent twin boundary, where is a preferential site for formation of PSB, a highcycle fatigue test is carried out at room temperature using a copper bicrystal specimen with the twin boundary. PSBs are observed near the boundary in the connection with the evolution of extrusion/intrusion on the specimen surface. The slip behavior is different from that predicted by the Schmid factor. A finite element method (FEM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In other words, the Schmid factor represents the ratio τ rss /σ 0 far away from grain boundaries (dissimilar interfaces). Therefore, the local slip behavior in a small-strain should be described by the stress field under the deformation-constraint among the grains (6)- (8) . Hence, Fig.…”
Section: Shear Stress On Crystallographic Slip Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, the Schmid factor represents the ratio τ rss /σ 0 far away from grain boundaries (dissimilar interfaces). Therefore, the local slip behavior in a small-strain should be described by the stress field under the deformation-constraint among the grains (6)- (8) . Hence, Fig.…”
Section: Shear Stress On Crystallographic Slip Systemmentioning
confidence: 99%
“…Under small strain of a polycrystal, slip deformation and crack initiation can be described by the magnitude of τ rss /σ 0 (6)- (8) . Hereafter, we discuss τ mrss as the representative stress that governs the strength of the micro-interconnection.…”
Section: Shear Stress On Crystallographic Slip Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the intrusions/extrusions observed in the experiments formed parallel to the Σ3 twin boundaries. Fatigue experiments performed on face-centered-cubic bulk metals with twin boundaries have demonstrated that persistent slip bands and subsequent intrusions/extrusions are preferentially formed at the slip system parallel to a Σ3 twin boundary [4][5][6][7]. This is due to stress concentration near the junction of a twin boundary and the surface, which is brought about by elastic mismatch between the crystals [6].…”
mentioning
confidence: 99%
“…Fatigue experiments performed on face-centered-cubic bulk metals with twin boundaries have demonstrated that persistent slip bands and subsequent intrusions/extrusions are preferentially formed at the slip system parallel to a Σ3 twin boundary [4][5][6][7]. This is due to stress concentration near the junction of a twin boundary and the surface, which is brought about by elastic mismatch between the crystals [6]. In freestanding Cu films, such stress concentrations occur on the twin boundary edges, resulting in formation of the intrusions/extrusions.…”
mentioning
confidence: 99%